Government Efforts to Address State Financial Losses Caused by Corruption Practices and Budget Misuse - Mohamad Ikbal Kadir; Muhammad Saleh Gasin; Wisma A. Rasid; Apriyni Melani Putri (Eastasouth Institute, 2026)
Corruption and budget misuse are serious problems that cause state financial losses and hinder national development. This study aims to analyze various government efforts to address these losses through legal, administrative, and preventive approaches. The method used is a literature review by examining laws and regulations as well as government policies. The results show that government efforts include law enforcement, asset recovery, bureaucratic reform, increased transparency, and anti-corruption education. Synergy among state institutions and public participation are important factors in the success of corruption eradication.